Gene Expression During the Development of Bacillus subtilis Bacteriophage φ29 I. Analysis of Viral-Specific Transcription by Deoxyribonucleic Acid-Ribonucleic Acid Competition Hybridization - Loskutoff, D. J. (1973)
The ribonucleic acid (RNA) specified by bacteriophage φ29 was analyzed to determine its composition at various times in the viral lytic cycle. Although viral-specific RNA was detected immediately after infection, a large increase in the rate was observed at 10 min when DNA synthesis began. φ29 was found to resemble other viruses in that gene expression occurred in two stages which could be defined temporally as “early” and “late.” Early RNA appeared before the onset of viral deoxyribonucleic acid (DNA) replication and accounted for approximately 40% of the viral genetic potential. This RNA was also present late in the infectious cycle because of the slow turnover rate of φ29-specific RNA (approximately 10 min half-life) and the continued synthesis of much early viral RNA throughout infection. Late RNA was first detected at approximately the same time as viral DNA replication, although late transcription was not dependent upon DNA synthesis. This RNA was only partially displaced by early RNA in the appropriate competition experiments, suggesting that it contained sequences not present in the early class. Expression of viral genes was sensitive to rifamycin throughout the lytic cycle, the sensitivity resulting from a dependence upon the rifamycin phenotype of the host RNA polymerase.